1994
DOI: 10.1111/j.1365-2958.1994.tb01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Information essential for cell‐cycle‐dependent secretion of the 591‐residue Caulobacter hook protein is confined to a 21‐amino‐acid sequence near the N‐terminus

Abstract: Recent findings suggest that axial flagellar proteins and virulence proteins of Gram-negative bacteria are exported from the cytoplasm via conserved translocation systems. To identify residues essential for secretion of flagellar axial proteins we examined the 591-residue Caulobacter crescentus flagellar hook protein. Western blot assays of the culture media of strains producing mutant hook proteins show that only residues 38-58 are essential for its secretion to the cell surface. We discuss the observation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 66 publications
4
41
0
Order By: Relevance
“…If FliE is exported, it should have regions of its sequence that constitute the recognition signal for its export by the flagellar apparatus. Other exported flagellar proteins (e.g., flagellin and hook protein) are recognized by N-terminal sequence (10,12). Consistent with this, FliE-V99G, with its mutation almost at the C terminus, was able to be exported, as judged by its ability to support the export of other substrates such as FlgD and to support motility, especially if overproduced and especially if in combination with the suppressor forms of FlgB.…”
Section: Flgb Is Probably the Most Proximal Of The Four Rod Proteinssupporting
confidence: 56%
“…If FliE is exported, it should have regions of its sequence that constitute the recognition signal for its export by the flagellar apparatus. Other exported flagellar proteins (e.g., flagellin and hook protein) are recognized by N-terminal sequence (10,12). Consistent with this, FliE-V99G, with its mutation almost at the C terminus, was able to be exported, as judged by its ability to support the export of other substrates such as FlgD and to support motility, especially if overproduced and especially if in combination with the suppressor forms of FlgB.…”
Section: Flgb Is Probably the Most Proximal Of The Four Rod Proteinssupporting
confidence: 56%
“…In agreement with this idea, Kuwajima et al (25) have shown that 183 residues of the N terminus of the E. coli flagellin are required for secretion. Likewise, a 21-amino-acid sequence near the N terminus of a Caulobacter flagellar hook protein is essential for secretion of this protein via the flagellum-specific pathway (23). Possibly the C terminus contains the information needed to secrete FlaA from V. anguillarum.…”
Section: Discussionmentioning
confidence: 99%
“…In the flagellum, the N-terminal parts of the flagellin or hook protein have been identified as secretion signals, albeit the very N-termini were not strictly required for secretion [187][188][189]. Both the identified minimal export signal of the flagellin and fulllength anti-s 28 factor FlgM have been successfully used as export signals for substrates which could subsequently cleaved by TEV protease [190,191].…”
Section: Export Signalsmentioning
confidence: 99%